Cost-effectiveness of cognitive–behavioural therapy for sleep disorder added to usual care in patients with schizophrenia: the BEST study - Apostolos Tsiachristas; Felicity Waite; Daniel Freeman; Ramon Luengo-Fernandez (BJPsych Open, 2018)
BackgroundSleep problems are pervasive in people with schizophrenia, but there are no clinical guidelines for their treatment. The Better Sleep Trial (BEST) concluded that suitably adapted cognitive–behavioural therapy (CBT) is likely to be highly effective, although its cost-effectiveness is unknown.AimsTo assess the potential cost-effectiveness of CBT for sleep disorders in patients with schizophrenia.MethodAn economic evaluation of the BEST study with a 6-month time horizon was used to establish the cost-effectiveness of CBT plus usual care in terms of costs per quality-adjusted life year (QALY) gained. Uncertainty was displayed on cost-effectiveness planes and acceptability curves. Value of information analysis was performed to estimate the benefits of obtaining further evidence.ResultsOn average, the treatment led to a 0.035 QALY gain (95% CI −0.016 to 0.084), and £1524 (95% CI −10 529 to 4736) and £1227 (95% CI −10 395 to 5361) lower costs from National Health Service and societal perspectives, respectively. The estimated value of collecting more information about the effects of the CBT on costs and QALYs was approximately £87 million.ConclusionsCBT for insomnia in people with schizophrenia is effective and potentially cost-effective. A larger trial is needed to provide clear evidence about its cost-effectiveness.RelevancePatients with schizophrenia have multiple complex health needs, as well as very high rates of depression, suicidal ideation and poor physical health. The results of this study showed that treating pervasive sleep problems in this patient group with cognitive–behavioural therapy (CBT) is very likely to improve patient quality of life in the short term. Clinicians most commonly use hypnotic medication to treat sleeping disorders. This study indicates that CBT may be an effective and cost-effective intervention in this patient group. This alternative would also be aligned with patient preferences for psychological and behavioural-type therapy.Declaration of interestNone.